مدى التزام المصارف التجارية بأبعاد المسؤولية الاجتماعية دراسة ميدانية في محافظة اللاذقية - قاسم, سامر (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى دراسة مدى التزام المصارف التجارية بأبعاد المسؤولية الاجتماعية (القانونية, الاقتصادية, الأخلاقية, الإنسانية). اعتمد البحث المنهج الوصفي, وشمل مجتمع البحث جميع العاملين في المصارف التجارية العامة والخاصة في محافظة اللاذقية, والبالغ عددهم تقريباً (671) عاملاً. تمّ تحديد حجم العينة بالاعتماد على قانون العينة الإحصائية, حيث بلغت (244) عاملاً تمّ توزيعها باستخدام التوزيع المتناسب بين المصارف العامة والخاصة. وُزعت الاستبانات على العاملين وأعيد منها (230) استبانة بنسبة استجابة بلغت (94.26%). وباستخدام الأساليب الإحصائية توصل البحث إلى النتائج الآتية:*تلتزم المصارف التجارية في محافظة اللاذقية بأبعاد المسؤولية الاجتماعية: القانونية, الاقتصادية, الأخلاقية, بدرجة عالية, وبأهمية نسبية بلغت (71.88%) للبعد الأخلاقي, و(77.68%) للبعد الاقتصادي, و(74.04%) للبعد الأخلاقي.* تلتزم المصارف التجارية في محافظة اللاذقية ببعد المسؤولية الإنسانية بدرجة متوسطة, وبأهمية نسبية بلغت (57.92%).*لا تختلف المصارف التجارية العامة والخاصة في درجة التزامها بأبعاد المسؤولية الاجتماعية: القانونية, والاقتصادية, والأخلاقية, والإنسانية.The research aims at studying the extent of commercial banks' commitment to the dimensions of social responsibility (legal, economic, moral, humanitarian). The research adopted a descriptive approach, Also the research community included all workers in the public and private commercial banks in the governate of Latakia, and of approximately (671) workers. The sample size was determined based on the statistical sample law, which has reached (244) workers and it has been distributed using the proportional distribution between public and private banks. The questionnaires were distributed to the employees, and (230) questionnaire were returned with a response rate (94.26%). Using statistical methods the results were as the following:*Commercial banks in the governate of Latakia are highly committed to dimensions of social responsibility, legal, economic, moral. The relative importance of the moral dimension is(71.88%), (77.68%) for the economic dimension, and (74.04%) for the moral dimension.*Commercial banks in Latakia governate is moderately committed to the humanitarian dimension of responsibility with the relative importance of (57.92%).*Public and private commercial banks do not differ in the degree of commitment to the dimensions of social responsibility: legal, economic, moral, and humanitarian.